Increased bone density and resistance to ovariectomy-induced bone loss in FoxP3-transgenic mice based on impaired osteoclast differentiation. - Zaiss, Mario; Sarter, Kerstin; Heß, Andreas; Engelke, Klaus; Boehm, Christina; Nimmerjahn, Falk; Voll, Reinhard; Schett, Georg; David, Jean-Pierre (Arthritis and Rheumatism, 2010)
OBJECTIVE Immune activation triggers bone loss. Activated T cells are the cellular link between immune activation and bone destruction. The aim of this study was to determine whether immune regulatory mechanisms, such as naturally occurring Treg cells, also extend their protective effects to bone homeostasis in vivo. METHODS Bone parameters in FoxP3-transgenic (Tg) mice were compared with those in their wild-type (WT) littermate controls. Ovariectomy was performed in FoxP3-Tg mice as a model of postmenopausal osteoporosis, and the bone parameters were analyzed. The bones of RAG-1(-/-) mice were analyzed following the adoptive transfer of isolated CD4+CD25+ T cells. CD4+CD25+ T cells and CD4+ T cells isolated from FoxP3-Tg mice and WT mice were cocultured with monocytes to determine their ability to suppress osteoclastogenesis in vitro. RESULTS FoxP3-Tg mice developed higher bone mass and were protected from ovariectomy-induced bone loss. The increase in bone mass was found to be the result of impaired osteoclast differentiation and bone resorption in vivo. Bone formation was not affected. Adoptive transfer of CD4+CD25+ T cells into T cell-deficient RAG-1(-/-) mice also increased the bone mass, indicating that Treg cells directly affect bone homeostasis without the need to engage other T cell lineages. CONCLUSION These data demonstrate that Treg cells can control bone resorption in vivo and can preserve bone mass during physiologic and pathologic bone remodeling.